Influence of physical and psychological stress on decision-making performance of soccer referees - Pizzera, A.; Laborde, S.; Lahey, J.; Wahl, P. (Journal of Sports Sciences, 2022)
Soccer referees have to make quick and accurate decisions while experiencing physical stress (i.e., fatigue) and psychological stress (i.e., pressure from the crowd). Researchers have examined the influence of physical and psychological stress on skilled referees` decision-making performance separately; however, referees usually experience both types of stress simultaneously. The aim of the study was to investigate the influence of both physical and psychological stress on skilled and less-skilled soccer referees` decision-making performance. To simulate the physical and psychological stress during a game, 25 referees were asked to make foul decisions while running on a treadmill and/or being exposed to auditory stress. Referees were more physically fatigued in the physical and psychologically stressed in the psychological stress condition. However, this only negatively influenced their decision-making performance in the video test during the submaximal physical stress condition, when compared to the resting condition. The results also indicate that the experienced referees learned to cope with fatigue and psychological stress regarding their cognitive processes. The effects seem to be differentially detrimental, depending on the league level of refereeing, but also whether physical and psychological stress are induced separately. The study protocol could help referees train in a simulated learning environment, besides on-field games.